Deciphering response dynamics and treatment resistance from circulating tumor DNA after CAR T-cells in multiple myeloma - Hitomi Hosoya; Mia Carleton; Kailee Tanaka; Brian Sworder; Shriya Syal; Bita Sahaf; Alisha M. Maltos; Oscar Silva; Henning Stehr; Vanna Hovanky; George Duran; Tian Zhang; et al. (Nature Communications)
Abstract Despite advances in treatments, multiple myeloma (MM) remains an incurable cancer where relapse is common. We developed a circulating tumor DNA (ctDNA) approach in order to characterize tumor genomics, monitor treatment response, and detect early relapse in MM. By sequencing 412 specimens from 64 patients with newly diagnosed or relapsed/refractory disease, we demonstrate the correlation between ctDNA and key clinical biomarkers, as well as patient outcomes. We further extend our approach to simultaneously track CAR-specific cell-free DNA (CAR-cfDNA) in patients undergoing anti-BCMA CAR T-cell (BCMA-CAR) therapy. We demonstrate that ctDNA levels following BCMA-CAR inversely correlate with relative time to progression (TTP), and that measurable residual disease (MRD) quantified by peripheral blood ctDNA (ctDNA-MRD) was concordant with clinical bone marrow MRD. Finally, we show that ctDNA-MRD can anticipate clinical relapse and identify the emergence of genomically-defined therapy-resistant clones. These findings suggest multiple clinical uses of ctDNA for MM in molecular characterization and disease surveillance.